The impact of perceived characteristics on technology adoption among Manufacturing Small and Medium Enterprises in Malaysia / Kogilavani Shanmugam and Jaya Kumar Shanmugam - Shanmugam, Kogilavani; Shanmugam, Jaya Kumar (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Technology adoption among SMEs in Malaysia is a crucial issue, and continuous examination needs to be conducted since SMEs play a dominant role in the nation's gross domestic products (GDP). This study aims to examine the impact of perceived characteristics on technology adoption among manufacturing SMEs in Malaysia. Rogers' diffusion of innovation and resource-based-view theory was used to build the research framework and hypothesis for this study. Among the targeted population of 380 respondents from the manufacturing sector, a total of 153 questionnaires were valid to use. In this study, the SPSS software was used to analyse the collected data. The finding shows that the five perceived characteristics, relative advantage, compatibility, complexity, trialability, and observability, positively impact technology adoption. Observability was the most influential element in technology adoption among the five characteristics. The result of this study provides a greater understanding for firms on the importance of technology adoption. At the end of this study, several recommendations and suggestions for further research are discussed.